A framework for plant growth analysis and simulation using data analysis techniques. Issue 4 (5th May 2020) - Mani, Gayathri; Chidambaranathan, Malathy; Sagi, Snehit
Abstract : Purpose: In India, agriculture is considered as the major source of income for a major sector of people. Our country's GDP (Gross Domestic Product) can increase only if we focus on agriculture and its growth toward global economy. There have been several attempts to improve the agricultural sector since decades. Design/methodology/approach: This work describes about the design of a device which continuously monitors the plant growth and sends the data to a centralized database, where data is dynamically analyzed based on base references using various machine learning algorithms like regression, gradient descent, clustering etc. Findings: This paper aims at analyzing the plant growth in of our country and focuses on the improvement of plant growth based on factors such as temperature, air moisture, radiant energy, carbon dioxide levels, soil pH& temperature through the design of a device. Originality/value: It is anticipated to provide a solution by analyzing the plant growth percentage in different regions over a period of time. Based on the inferences, we will be able to suggest an optimum environment for the plant species to grow best. Various sensors like temperature and humidity sensors, light sensors and pH electrodes can be used in collecting data from the plant environment.